2013
DOI: 10.1371/journal.pone.0066562
|View full text |Cite
|
Sign up to set email alerts
|

The Applicability of TaqMan-Based Quantitative Real-Time PCR Assays for Detecting and Enumerating Cryptosporidium spp. Oocysts in the Environment

Abstract: Quantitative real-time polymerase chain reaction (qPCR) assays to detect Cryptosporidium oocysts in clinical samples are increasingly being used to diagnose human cryptosporidiosis, but a parallel approach for detecting and identifying Cryptosporidium oocyst contamination in surface water sources has yet to be established for current drinking water quality monitoring practices. It has been proposed that Cryptosporidium qPCR-based assays could be used as viable alternatives to current microscopic-based detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
(55 reference statements)
0
21
0
7
Order By: Relevance
“…For the detection of low levels of flow cytometrysorted C. parvum oocysts seeded in fecal specimens or water concentrates, the 18S-LC2 and hsp90 assays could detect a single oocyst, indicating that it is possible for these two assays to detect low levels of oocysts in water samples. A recent study comparing the sensitivities and specificities of 10 TaqMan-based real-time PCR assays showed that 8 of the assays could reliably detect 10 flow cytometry-sorted oocysts in reagent water or an environmental matrix (26). Therefore, the 18S-LC2 and hsp90 real-time PCR genotyping assays developed in this work likely have higher sensitivities in detecting Cryptosporidium oocysts in water and thus can be potentially used as rapid genotyping tools for environmental monitoring.…”
Section: Discussionmentioning
confidence: 90%
“…For the detection of low levels of flow cytometrysorted C. parvum oocysts seeded in fecal specimens or water concentrates, the 18S-LC2 and hsp90 assays could detect a single oocyst, indicating that it is possible for these two assays to detect low levels of oocysts in water samples. A recent study comparing the sensitivities and specificities of 10 TaqMan-based real-time PCR assays showed that 8 of the assays could reliably detect 10 flow cytometry-sorted oocysts in reagent water or an environmental matrix (26). Therefore, the 18S-LC2 and hsp90 real-time PCR genotyping assays developed in this work likely have higher sensitivities in detecting Cryptosporidium oocysts in water and thus can be potentially used as rapid genotyping tools for environmental monitoring.…”
Section: Discussionmentioning
confidence: 90%
“…Embora esta metodologia seja útil no monitoramento ela é incapaz de diferenciar entre espécies ou determinar infectividade dos oocistos presentes no ambiente aquático. Assim, as técnicas moleculares são alternativas promissoras para caracterização das espécies do parasito (STAGGS et al, 2013).…”
Section: Análise De Especificidade Dos Iniciadores E Sondaunclassified
“…A qPCR é um sistema adaptado para detecção de sequências alvo que permite a determinação da variabilidade genética entre os isolados e medir a quantidade relativa de DNA acumulada ao final dos ciclos da reação (GUY et al, 2003;STOUP et al, 2006;ALONSO et al, 2011;RYU et al, 2010;STAGGS et al, 2013).…”
Section: Introdução 26unclassified
See 2 more Smart Citations